2022
DOI: 10.1111/bcp.15342
|View full text |Cite
|
Sign up to set email alerts
|

Fixed dosing of kukoamine B in sepsis patients: Results from population pharmacokinetic modelling and simulation

Abstract: Aims To assess the appropriateness of the body weight or fixed dosing regimen, a population pharmacokinetic (PopPK) model of kukoamine B has been built in sepsis patients. Methods Plasma concentrations of kukoamine B and the covariates information were taken from 30 sepsis patients assigned into 0.06 mg/kg, 0.12 mg/kg and 0.24 mg/kg groups in a Phase IIa clinical trial. The PopPK model was built using a nonlinear mixed‐effect (NLME) modelling approach. Based on the final model, PK profiles were respectively si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In addition, the choice of nalbuphine dosage regimens is also an issue worth to be discussed. Wang et al (2022) found that the PK variability of the drug was lower for fixed-dose dosage regimens than that for weight-based dosage regimens. Previous studies had shown that weight of neonates and children is a significant factor affecting nalbuphine PK behavior ( Jacqz-Aigrain et al, 2003 ; Bressolle et al, 2011 ).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, the choice of nalbuphine dosage regimens is also an issue worth to be discussed. Wang et al (2022) found that the PK variability of the drug was lower for fixed-dose dosage regimens than that for weight-based dosage regimens. Previous studies had shown that weight of neonates and children is a significant factor affecting nalbuphine PK behavior ( Jacqz-Aigrain et al, 2003 ; Bressolle et al, 2011 ).…”
Section: Introductionmentioning
confidence: 97%